2023
DOI: 10.2174/1570159x20666221012121534
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Physiological Correlates of the Bidirectional Fear Phenotype of the Carioca Rats and Other Bidirectionally Selected Lines

Abstract: The Carioca rat lines originated from the selective bidirectional breeding of mates displaying extreme defense responses to contextual conditioned fear. After three generations, two distinct populations could be distinguished: the Carioca High- and Low-conditioned Freezing rats, CHF, and CLF, respectively. Later studies identified strong anxiety-like behaviors in the CHF line, while indications of impulsivity and hyperactivity were prominent in the CLF animals. The present review details the physiological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 188 publications
0
4
0
Order By: Relevance
“…Finally, other studies developed by our group but not discussed in the scope of this review (for details, see Dias et al, 2014 ; Lages et al, 2023 ; Léon et al, 2020 ) also indicate functional and structural changes in neural circuits underlying anxiety in the CHF rat line, which seems to indicate that the phenotyping process that strengthened this trait anxiety was also expressed in terms of a great capacity for neural plasticity.…”
Section: Chf Rat Line As a Model Of Gadmentioning
confidence: 55%
“…Finally, other studies developed by our group but not discussed in the scope of this review (for details, see Dias et al, 2014 ; Lages et al, 2023 ; Léon et al, 2020 ) also indicate functional and structural changes in neural circuits underlying anxiety in the CHF rat line, which seems to indicate that the phenotyping process that strengthened this trait anxiety was also expressed in terms of a great capacity for neural plasticity.…”
Section: Chf Rat Line As a Model Of Gadmentioning
confidence: 55%
“…Interestingly, increased TNF-ɑ in the AMG is associated with altered levels of glutamate in this same nucleus, disturbances in learning and increased fear responses, which can contribute to the impaired fear extinction seen in psychiatric disorders [ 23 , 38 ]. Indeed, increased EAAT-2 expression (a major glutamate transporter expressed predominantly in astrocytes) has been reported in association with increased fear responses and is relevant to psychiatric and neurological disorders [ 39 , 40 ]. In line with these findings, our study observed increased astrocyte and EAAT-2 expression in the amygdala of MA animals, suggesting altered these to be involved in the presentation of maladaptive avoidance behaviour and expression of exacerbated fear responses.…”
Section: Discussionmentioning
confidence: 99%
“…3) Different pattern of acquisition/extinction in response to context and cue; 4) Increased corticosterone serum levels; 5) Benzodiazepine and serotonergic anxiolytics attenuate freezing behavior in CHF but not CLF rats; and 6) Higher alcohol intake. CHF rats have also shown parallel changes in the function and structure of neural circuits thought to underlie anxiety (Dias et al, 2014;Lages et al, 2023;León et al, 2020).…”
Section: The Carioca Model Of Trait Anxietymentioning
confidence: 99%
“…Their Table 1 maps CHF rats to human generalized anxiety in terms of (their words): 1) High and diffuse anxiety in contextual fear conditioning, elevated plus maze, and avoidance behavior in the elevated T-maze; 2) Immobility/freezing behavior; 3) Different pattern of acquisition/extinction in response to context and cue; 4) Increased corticosterone serum levels; 5) Benzodiazepine and serotonergic anxiolytics attenuate freezing behavior in CHF but not CLF rats; and 6) Higher alcohol intake. CHF rats have also shown parallel changes in the function and structure of neural circuits thought to underlie anxiety (Dias et al, 2014 ; Lages et al, 2023 ; León et al, 2020 ).…”
Section: Strain Derivation – Personality In Ratsmentioning
confidence: 99%